Research and Application of Support Resistant Limiting Dampers in the Deep-Buried Large-Section Loess Tunnel - Yong Deng; Jiangsheng Xie; Shuguang Li (Advances in Civil Engineering)
The paper aims to solve the problem that the primary support of the deep-buried large-section loess tunnel of the Haolebaoji-Ji’an Railway was damaged due to excessive force. Based on indoor tests, on-site construction feedback, and monitoring measurement data, the surrounding rock deformation and structural forces with different support schemes were compared and analyzed. The engineering application methods and mechanism of the support resistant limiting damper (SRLD) technology were studied. The results show that for the deep-buried large-section loess tunnels, under the premise of ensuring the self-supporting capacity of the surrounding rock is not significantly reduced, and the loose pressure is not significantly increased, the resistance-limiting and high-ductility support concept that can control the deformation and the energy release of the surrounding rock is reasonable and feasible. The support resistant limiting damper (SRLD) is a reasonable and practical resistance-limiting and high-ductility support method, which successfully solved the failure of the primary support of the deep-buried large-section loess tunnel. The SRLD’s integrity and safety are guaranteed, the materials are easy to obtain, the processing is convenient, and the construction is simple and easy to operate. The SRLD is a safe and economic support structure.